Morphotype Analysis of Endophytic Fungus Isolated from Taxus sumatrana of Mount Singgalang, West Sumatra Region - Sari, Wulan Komala; Periadnadi, Periadnadi; Nurmiati, Nurmiati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Taxus sp. plants in temperate climates like Europe and America have been extensively studied and identified as promising sources of endophytic microbes that produce anticancer compounds such as Taxol. These endophytic microbes exhibit high adaptability to the specific growing conditions of their host plants. Research has highlighted metabolic differences between tropical and temperate endophytes. The presence of Taxus sumatrana plants in tropical areas like Mount Singgalang in West Sumatra, Indonesia was subjected to explore potential new sources of bioactive compounds from tropical microbes. This research aims to identify the morphotypes of endophytic fungi isolated from the barks of Taxus sumatrana plants originating from Mount Singgalang. The method used is small pieces of the inner bark of Taxus sumatrana were placed on the surface of growth medium (PDA). The small hyphae emerging from the piece of plant samples were regularly monitored for the morphological characteristics of the colony and conidia structure. Each fungal culture was checked for purity and transferred to another PDA plate by the hyphal tip method. The investigation isolated two endophytic fungi from the bark of Taxus sumatrana: Pestalotiopsis microspora and Neopestalotiopsis sp.